Long non-coding RNA TUG1: a novel therapeutic target in small cell lung cancer - Ou, Chunlin; Li, Guiyuan (Journal of Thoracic Disease, 2017)
Lung cancer is the leading cause of cancer deaths worldwide (1), and its development and progression is a multi-stage and multi-gene process. Small cell lung cancer (SCLC) accounts for 10–15% of cases (2) and has the following characteristics: a high growth fraction, a rapid doubling time, and early development of widespread metastases (3).